E-Service Quality, Trust, Emotions, and Forgiveness Drive Repurchase in M-Commerce - Tullaili, Mufida; Susanto, Perengki (Academia Open, 2025)
General Background: With the rapid evolution of technology and increasing reliance on the internet, mobile commerce (M-Commerce) has become a dominant channel for consumer transactions. Specific Background: Within this context, the quality of electronic services (E-Service Quality) and associated factors such as E-Trust, Complaint Handling, and Relationship Quality have become critical to fostering consumer loyalty. Knowledge Gap: However, limited research has examined the simultaneous effects of these factors alongside Consumers’ Negative Emotions and Forgiveness on Repurchase Intention in M-Commerce. Aims: This study aims to investigate the influence of E-Service Quality, E-Trust, Complaint Handling, Relationship Quality, Negative Emotions, and Forgiveness on Repurchase Intention among M-Commerce users. Results: Using a quantitative survey of 384 respondents in West Sumatra, Indonesia, and analysis tools including SmartPLS and SPSS 26, the findings reveal that E-Service Quality significantly enhances E-Trust and Repurchase Intention. E-Trust itself is a pivotal predictor of repurchase behavior. Negative emotions harm Relationship Quality and subsequently repurchase intentions, although strong relationship quality can mitigate these effects. Novelty: This study integrates emotional and relational variables in a unified M-Commerce model. Implications: The results underscore the importance of maintaining high service quality, trust, and complaint management strategies to retain customers and counteract emotional disruptions. Highlights: Highlights the role of E-Trust in driving repurchase behavior. Integrates emotional and relational factors into M-Commerce research. Emphasizes complaint handling as a trust-building strategy. Keywords: E-Service Quality, E-Trust, Complaint Handling, Repurchase Intention, M-Commerce